SHetA2 interference with mortalin binding to p66shc and p53 identified using drug-conjugated magnetic microspheres - Benbrook, Doris Mangiaracina (Springer US, 2013)
SHetA2 is a small molecule flexible heteroarotinoid (Flex-Het) with promising cancer prevention and therapeutic activity. Extensive preclinical testing documented lack of SHetA2 toxicity at doses 25 to 150 fold above effective doses. Knowledge of the SHetA2 molecular target(s) that mediate(s) the mechanism of SHetA2 action is critical to appropriate design of clinical trials and improved analogs. The aim of this study was to develop a method to identify SHetA2 binding proteins in cancer cells. A known metabolite of SHetA2 that has a hydroxyl group available for attachment was synthesized and conjugated to a linker for attachment to a magnetic microsphere. SHetA2-conjugated magnetic microspheres and unconjugated magnetic microspheres were separately incubated with aliquots of a whole cell protein extract from the A2780 human ovarian cancer cell line. After washing away non-specifically bound proteins with the protein extraction buffer, SHetA2-binding proteins were eluted with an excess of free SHetA2. In two independent experiments, an SDS gel band of about 72 kDa was present at differential levels in wells of eluent from SHetA2-microspheres in comparison to wells of eluent from unconjugated microspheres. Mass spectrometry analysis of the bands (QStar) and straight eluents (Orbitrap) identified mortalin (HSPA9) to be present in the eluent from SHetA2-microspheres and not in eluent from unconjugated microspheres. Co-immunoprecipitation experiments demonstrated that SHetA2 interfered with mortalin binding to p53 and p66 Src homologous-collagen homologue (p66shc) inside cancer cells. Mortalin and SHetA2 conflictingly regulate the same molecules involved in mitochondria-mediated intrinsic apoptosis. The results validate the power of this protocol for revealing drug targets. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10637-013-0041-x) contains supplementary material, which is available to authorized users.